Sensitivity of Septoria pyricola isolates to carbendazim, DMI and QoI based fungicides and to boscalid, in Greece - PAPPAS, Athanassios; VELLIOS, Evangelos; MYLONOPOULOS, Ioannis; CHATZIDIMOPOULOS, Michalis; VLASSACOUDIS, Apostolos (Phytopathologia Mediterranea, 2010)
The sensitivity of 36 Septoria pyricola single spore isolates, obtained from isolated pear orchards, to carbendazim, bitertanol, flusilazole, myclobutanil, azoxystrobin, kresoxim-methyl, pyraclostrobin, trifloxystrobin and boscalid, was studied in vitro. Spore suspensions were point-inoculated on media amended with various concentrations of fungicides and the minimum inhibitory concentration (MICs) of the fungicides was determined. Most isolates were highly resistant to carbendazim, forming colonies even at concentrations of 100 mg L-1 of the fungicide. A few isolates failed to form colonies with carbendazim concentrations of 0.1 and 10 mg L-1; these isolates were designated carbendazim-sensitive and moderately carbendazim-resistant respectively. The MIC of DMI fungicides was up to 1 mg L-1 with some isolates, and the mean MICs of bitertanol, flusilazole and myclobutanil were 0.133±0.036, 0.075±0.044 and 0.230±0.038 mg L-1 respectively. The MIC of the QoI fungicides was up to 0.1 mg L-1 with most isolates, but some isolates were 100-fold less sensitive to azoxystrobin. The mean MICs of azoxystrobin, kresoxim-methyl, pyraclostrobin and trifloxystrobin were 0.177±0.040, 0.075±0.035, 0.067±0.063, and 0.073±0.065 mg L-1 respectively. Overall, the MIC of boscalid was 1 mg L-1, and the mean MIC was 0.111±0.044 mg L-1. The ED50 values of representative isolates are also presented, as determined by colony formation with dispersed spore inoculation on a medium amended with fungicides. The results show that the benzimidazoles are ineffective against S. pyricola isolates in Greece and suggest that the future effectiveness of the DMIs is at risk.